12 Stops Through Biblical History (The Biblical archaeology review, 2020)
In light of the global pandemic, museums throughout the world closed their physical doors. Yet rather than pausing their educational mission, many opened up their collections to be explored and enjoyed digitally. Even if you are confined within your home, you can virtually tour some of the world’s top museums.